Pengaruh Pemberian Cookies Ikan Teri (Stolephorus Sp) Terhadap Pencegahan Stunting pada Batita di Dusun I Paluh Mardan Desa Pematang Cengal Kec. Tanjung Pura Kab. Langkat Tahun 2023 - Fitriyani Pulungan; Lestari Lestari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Stunting is a child's body posture that is shorter when compared to children of his age. Body length for age is an indicator of chronic malnutrition. The incidence of stunting is influenced by several factors such as energy intake, nutrition, gender, number of members in the family, father's and mother's education, father's and mother's occupation, birth weight and family's economic status. The prevalence of stunting according to WHO (World Health Organization) in 2020 is 22% or 149.2 million children.Methods : The purpose of this study was to determine the effect of giving anchovy cookies (Stolephorus Sp) on the prevention of stunting in two-year-old infants in Hamlet I Paluh Mardan, Pematang Cengal Village, Tanjung Pura District, Langkat Regency in 2023. This research is a Quasi-Experimental study designed with a one group pretest and posttest design and examined 28 people as the research sample.Results and Discussion: The results of the study in the experimental group obtained results: the increase in the height of the male two-year-old baby was 1.1778 cm, the mean height was 89.4 cm; whereas for female toddlers, the average increase in body height was 1.1526 cm, with an average height of 90.6 cm. Meanwhile, the results of the analysis using the t-dependent test with a 95% confidence level showed a sig (2-tailed) value <0.05, which means that the effect of giving anchovy cookies was found on stunting prevention in toddlers.Conclusion: It is hoped that the residents of Hamlet I Paluh Mardan, Pematang Cengal Village, will utilize anchovies, processed into cookies or other processed forms, to increase the height of a 2 year old baby to prevent stunting, and future researchers will use my thesis as a reference.